Triggering regime change: A comparative analysis of the performance of innovation platforms that attempted to change the institutional context for nine agricultural domains in West Africa. (September 2018) - Hounkonnou, Dominique; Brouwers, Jan; van Huis, Arnold; Jiggins, Janice; Kossou, Dansou; Röling, Niels; Sakyi-Dawson, Owuraku; Traoré, Mamoudou
Abstract: The article synthesises the experiences of innovation platforms (IPs) that engaged in open-ended experimental action to improve the institutional context for smallholder farm development in West Africa. The IPs sought change at the level of the institutional regime covering an entire agricultural domain (such as cocoa, cotton, oil palm or water management). Their purpose was therefore not to 'roll out' farm-level technologies across rural communities. The IPs's outcomes were documented and analysed throughout by means of theory-based process tracing in each of seven of the nine domains in which regime change was attempted. The evidence shows that by means of exploratory scoping and diagnosis, socio-technical and institutional experimentation, and guided facilitation IPs can remove, by-pass, or modify domain-specific institutional constraints and/or create new institutional conditions that allow smallholders to capture opportunity. The article describes the 5-year, €4.5 million research programme in Benin, Ghana and Mali, covering theory, design, methods and results. It is the sequel to Hounkonnou et al. in AGSY 108 (2012): 74–83. Highlights: Purposeful institutional innovation has been ignored. This article is a major empirical research contribution. Action research can support institutional experiments that create space for innovation. AR4D can move beyond rolling out technologies and engage in 'scaling up' to create enabling conditions for innovation. Innovation platforms are not a magic bullet but they can create niches that durably affect institutional regimes Agricultural domains are best seen as arenas for negotiation and concerted action among stakeholders.